Pengaruh Pemberian Ekstrak Adas (Foeniculum vulgare Mill ) Pada Tikus Laktasi Terhadap Sel Neuroglia Anak Tikus - Dwi Ningsih (Jurnal Farmasi Indonesia, 2020)
Breast Milk is a natural baby food that is rich in nutrients and contains higher immunological factors compared to formula milk. Foeniculum vulgare Mill plants have long been used by the community as enhancing the production of breast milk (ASI). The purpose of this study was to determine the effect of lactogogum extracts of Foeniculum vulgare Mill leaves and stems in lactation mice, as seen from mouse neuroglia cells. Foeniculum vulgare Mill extract was made by maceration method using 96% ethanol solvent. The test animals used in the study were white rats, divided into 6 groups namely, normal control, control without drugs (cmc-na 0.5%), comparison of asifit drugs (67.86 mg / KgBB), ethanol extract groups of leaves and stems fennel dosage 315 mg / kg body weight, 630 mg / kg body weight, and 945 mg / kg body weight. The results of the research that have been done show that the ethanol extract of Foeniculum vulgare Mill leaves and stems dose 315 mg / kg body weight, 630 mg / kg body weight, and 945 mg / kg body weight have a lactagogum effect seen from the parameters of the number of glia cells in the brains of breastfed mice. The effect increase is not as large as the dose increase given. The ethanol extract of Adas leaves and stems of 630 mg / kg BW has an optimal lactagogum effect equivalent to drug control on the market as seen from the parameters of the number of glia cells in the brains of breastfed rat.